USP8 maintains embryonic stem cell stemness via deubiquitination of EPG5 - Haifeng Gu (Nature Portfolio, 2019)
Autophagy is implicated in self-renewal of stem cells, including embryonic stem cells (ES cells). Here the authors demonstrate EPG5 is highly expressed in ES cells, and its deubiquitylation by USP8 stimulates its interaction with LC3 to promote autophagy and maintenance of stemness.